Attention, locomotor activity and developmental milestones in rats prenatally exposed to ethanol. Issue 38 (2nd September 2014) - Brys, Ivani; Pupe, Stéfano; Bizarro, Lisiane
Abstract: Rationale: Decline of attentional performance as a function of time engaged on a task and hyperactivity are features shared by children and adults with fetal alcohol syndrome or attentional deficit and hyperactivity disorders. Objective: To investigate the effects of prenatal exposure to two doses of ethanol on developmental milestones, locomotor activity and attention. Methods: Wistar rats born from dams exposed to one of four maternal treatments during pregnancy were used: A35 – liquid diet with 35% ethanol‐derived calories; A10 – liquid diet with 10% ethanol‐derived calories; control – ethanol‐free liquid diet; chow – laboratory chow and water. Results: A35 performed worse in grip strength than control and chow (postnatal day – 14, p < 0.05) but not in negative geotaxis (postnatal days 7–10); A35 also showed more locomotor activity than control and A10 ( p < 0.05). Regarding attention, acquisition of the five choice reaction time task was similar between groups, but, the percentage of omission errors from A35 group was greater than other groups at baseline parameters, at shorter (2 s) and longer (7 s) inter‐trial intervals and at a shorter stimulus duration (0.5 s) ( p < 0.05). The percentage of omissions was larger in A35 as the blocks progressed in sessions with either longer or shorter inter‐trial intervals (group × block p < 0.05). Animals from A10 group did not show any impairment in the tasks performed. Conclusions: Our study demonstrates that as well as developmental impairments, prenatal ethanol can produce deficits associated with an increase in attentional demand in rodents, analogous to those observed in fetal alcohol syndrome and attentional deficit and hyperactivity disorders.